Perancangan Filter Gravityfed Untuk Saringan Air Kotor di Wilayah Desa Pedalaman Kabupaten Asahan Peranggan Ujung - Handoko, Wiwin; Ananda, Ricki (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Clean water is one of the necessities for humans, especially to meet the washing needs of families. Most of the population in the Asahan district still uses drilled well water as a source of clean water to meet their water needs. The results from inhalation of water will also be filtered, and usually, within 30 minutes, the water will turn yellow again. During this time, the cleaning of the water filtering container is cleaned every 1 - 2 weeks, with a long cleaning time of 30 minutes to 1 hour. From the field study, the research team designed a filter by utilizing six paralon pipes with a size of 3.5 inc, 1 m long, with a clarification module for each pipe, starting from the first pipe with spongy media, the second pipe for gravel media, the third medium, soil, and sand. The fourth media is charcoal, the fifth media, and the sixth paralon, and the sixth media is palm fiber. The results of the water reading in the first pipe to the fourth pipe found the ph of water at an index of 5-6 ph, with an average sensor output voltage value of 4787 mV. The sensor supply and the pH reader controller use a 7.4 VDC supply voltage and a 5VDC / 5A.